(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Vital statistics such as birth rate, maternal mortality, infant mortality, birth weight, fertilit y rate and infant morbidity are the major indicators of health, in the maternity care services. Birth weight is an important indicator in maternity care. It is the most sensitive and reliable indicator of the risk to the survival and its healthy growth and development. Birth weight is defined as the first weight taken of an infant, live or still born, preferably within one hour of birth ( Lalitha K, 1989)1. The normal birth weight is 2500 grams or more. Birth weight less than 2500 grams irrespective of gestational age is low birth weight. 1 Low birth weight is one of the most important causes for the high infant mortality rate. Survey reveals that, 15.3% of the infant mortality rate is caused due to low birth weight ( Population Council New York, 2002). 4Twenty two million low birth weight babies are born in the world, 90% belongs to the developing countries In India, the incidence of low birth weightis40%. In the rural areas low birth weight varies from 30 to 31%.